2015
DOI: 10.4236/ajps.2015.614233
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Peanut (Arachis hypogea L.) Cultivars as Revealed by RAPD Markers

Abstract: The objectives of this study were to evaluate the genetic diversity of the peanut accessions using Random Amplified Polymorphic DNA (RAPD) molecular marker and to evaluate RAPD markers to be used in peanut as genetic markers and improve such techniques as suitable strategies for peanut germplasm characterization. Twenty peanut accessions were included in this study and were subjected to RAPD molecular markers analysis. Twenty-seven RAPD primers produced 210 amplification products of which 80 (36.4%) were polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…DNA was extracted from fresh leaves (oldest two leaves on the plant) of the mother plant and seven acclimatized plants (two or three plants every treatment) resulted from the best treatments of in vitro shoot multiplication (3 mg · L -1 BA + 1 mg · L -1 NAA, 1.5 mg · L -1 TDZ + 0.5 mg · L -1 NAA, and 1.5 mg · L -1 TDZ + 1 mg · L -1 NAA) by cetyltrimethylammonium bromide according to Doyle and Doyle (1990). Polymerase chain reaction (PCR) was performed and repeated three times using six random decamer primers (Table 1) (Al-Saghir and Abdel-Salam, 2015;Joshi et al, 2009). RAPD-PCR was carried out in presence of 1· Taq DNA polymerase buffer (10 mM Tris-HCl of pH 8.3, 50 mM KCl, 1.5 mM MgCl 2 ), 100 mM dNTPs, 5 pmol single random primers, 25 ng DNA template, and 0.5 unit of Taq DNA polymerase in a total volume of 25 mL.…”
Section: Methodsmentioning
confidence: 99%
“…DNA was extracted from fresh leaves (oldest two leaves on the plant) of the mother plant and seven acclimatized plants (two or three plants every treatment) resulted from the best treatments of in vitro shoot multiplication (3 mg · L -1 BA + 1 mg · L -1 NAA, 1.5 mg · L -1 TDZ + 0.5 mg · L -1 NAA, and 1.5 mg · L -1 TDZ + 1 mg · L -1 NAA) by cetyltrimethylammonium bromide according to Doyle and Doyle (1990). Polymerase chain reaction (PCR) was performed and repeated three times using six random decamer primers (Table 1) (Al-Saghir and Abdel-Salam, 2015;Joshi et al, 2009). RAPD-PCR was carried out in presence of 1· Taq DNA polymerase buffer (10 mM Tris-HCl of pH 8.3, 50 mM KCl, 1.5 mM MgCl 2 ), 100 mM dNTPs, 5 pmol single random primers, 25 ng DNA template, and 0.5 unit of Taq DNA polymerase in a total volume of 25 mL.…”
Section: Methodsmentioning
confidence: 99%
“…These results agreed with Guo et al (2005) and Lang and Hang (2007) who reported that the distinctive RAPD patterns generated from peanut cultivars could be used as genomic fingerprint to establish the identity of a given genotype. Similarly, Al-Saghir and Abdel-Salam (2015) observed that the technique of RAPD could be used to detect the genetic diversity in peanut and give a successful fingerprinting of peanut using these markers. Lom and Rao (2015) indicated the efficacy of RAPD markers for detecting the genetic variability in the wild Musa acuminate.…”
Section: Rapd-pcr Analysismentioning
confidence: 96%
“…Application of RAPD markers in peanuts aid in determining the markers associated with genes controlling important traits. These molecular techniques assist in the identification of new and various sources of diversity which may aid breeders to choose what genotypes for creating new genetic combinations and to determine which genetic resources should be retained in a collection in order to conserve maximum genetic variation in the gene bank (Al-Saghir and Abdel-Salam 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Breeders around the world have successfully developed hundreds of improved peanut cultivars by making use the diversity in peanut germplasm. The diversity has allowed breeders to better understand the evolutionary relationships among accessions, to sample germplasm in a more systematic fashion, and to develop strategies to incorporate useful diversity in their breeding programs (Al-Saghrir & Abdel-Salam, 2015).…”
Section: Introductionmentioning
confidence: 99%